Experimental investigation of the pore fractal characteristics and damage degradation mechanism of sandstone after cyclic Freeze‒thaw treatments - Ke Ou; Changsong Wang; Ri-hong Cao; Hang Lin; Lei Fang (Journal of Materials Research and Technology, 2023)
To reveal the microscopic pore characteristics and strength weakening mechanism of rock under the influence of cyclic freeze-thaw treatment, uniaxial compression tests and MIP (mercury intrusion porosimetry) were conducted on red sandstone specimens with different numbers of freeze-thaw cycles (0, 20, 40, 60, and 80). The experimental results showed that cyclic F-T (freeze-thaw) treatment can lead to an increase in porosity and the expansion of the pore structure. Specifically, the porosity increased by nearly 30.22% from 8.467% without freeze-thaw to 11.026% after 80 freeze-thaw cycles. The distribution ratios of mesopores (2–10 μm) and micropores (less than 0.1 μm) changed from 0.7% to 19.9% without freeze‒thaw to 12.6% and 11.6% after 80 freeze‒thaw cycles, which showed an expansion trend from small to large pores. For the PFD (pore fractal dimension) of sandstone, three fractal models (capillary pressure model, Menger sponge model and thermodynamic model) were used to calculate the pore fractal dimension of different freeze-thaw cycles, which gradually increased with the increase in freeze‒thaw cycles. Specifically, the PFD increased by 3.02, 3.01 and 2.65% after 20, 40, 60, and 80 freeze-thaw cycles, respectively. Additionally, the PFD calculated by the capillary pressure model and Menger sponge model had piecewise characteristics, which can better characterize pore fractal characteristics with pore diameters less than 2 μm. In summary, based on thermodynamic theory and pore water frost heaving deformation theory, a freeze-thaw damage degradation model based on the porosity of a fractured rock mass was established, and the theoretical value obtained was in good agreement with the experimental results.